UJI DAYA HAMBAT EKSTRAK ETANOL DAUN MIANA MERAH (Coleus benth) TERHADAP Staphylococcus aureus - dzulasfi; Yusriyani; Riska Yuliastuti. K (Akademi Farmasi Yamasi Makassar, 2023)
Research has been carried out to test the inhibitory power of the ethanolic extract of red miana leaves (Coleus benth) against Staphylococcus aureus. This study aims to determine the inhibition test of the ethanolic extract of red miana leaves against Staphylococcus aureus. The prepared miana leaf extract was then tested for the inhibition test of the ethanol extract against Staphylococcus aureus using the well method. The results obtained produced an inhibition zone around the well with different diameters in each sample. The average diameter of the inhibition zone obtained from each sample of miana leaf extract preparations where with a concentration of 10%: -, 15%: 1mm and 20%: 1mm. From the test results can be obtained that the leaf extract of miana (Coleus benth) can inhibit the growth of Staphylococcus aureus with concentrations of 15% and 20%.